(untitled) (Research, Society and Development, 2023)
This in vitro study aimed to evaluate the effect of toothbrushing simulated test on wear and roughness of different low-viscosity resin composite, as well as the polymerization shrinkage stress. Thirty rectangular specimens (5 × 10 × 3 mm) were prepared and assigned into three different low-viscosity resin composites (n=10): Filtek flow Z350 (Z350); NanovaPro fill (Nanova), and SureFil SDR Flow (SDR). The specimens were brushed for 100.000 cycles using a toothbrushing testing machine with soft bristle tips (Colgate Classic, Colgate-Palmolive Co., Osasco, Sao Paulo, Brazil) and dentifrice suspension (Colgate MFP, Colgate-Palmolive Co.) in deionized water under a 300 g load. The surface roughness (Ra) (n=10) (before and after brushing) and wear (mm) (n=10) were measured by roughness tester. Also, the microhardness (KHN) (n=5) and shrinkage stress (MPa) (n=5) were evaluated. Data were analyzed by one-way for wear, microhardness and shrinkage stress data and two-way for roughness ANOVA and Tukey test (α = 0.05). The Nanova group presented higher final roughness (1.79±0.36) (p < 0.031), wear (13.87±3.26) (p <0.001) and microhardness (52.56±1.7) than the other groups (p < 0.006). For tensile test, all materials showed no difference in relation to shrinkage stress (p= 0.468). The Nanova group showed higher wear and roughness than the other groups. SDR and Z350 were statistically more resistant to wear.